Religio-philosophical discourses in the Mediterranean world : from Plato, through Jesus, to late antiquity - Petersen, Anders Klostergaard.; Kooten, Geurt Hendrik van, 1969- (Ancient Philosophy & Religion, 2017)
This first volume of the new Brill series "Ancient Philosophy andamp; Religion" is a collection of articles by scholars of Classics, Ancient Philosophy, and Ancient Judaism and Early Christianity. The articles are based on papers presented at two colloquia on the interface between Ancient Philosophy and Religion at the universities of Aarhus and Cambridge. They focus extensively on Platonic philosophy and piety and sketch an emerging religio-philosophical discourse in ancient Judaism (both in the Sibylline Oracles and 4 Maccabees). Furthermore, this volume studies Seneca's religio-philosophical understanding of 'consolation', compares early depictions of Jesus with those of ancient philosophers, and, finally, reconsiders responses of pagan philosophers to Christianity from the second century to Late Antiquity.